The Effect of Sintering Temperature on Wear Resistance of Alloys Produced by Using Hot Isostatic Pressing (HIP) Method - Yildiz, Tuelay; Aba, Sueleyman (Pleiades Publishing Ltd, 2019)
The present study investigated the effect of the temperature, at which a new matrix material was produced via hot isostatic pressing (HIP) method by adding certain rate of Co and Ni elements into CuSn (85/15) bronze alloy, and Co and Ni elements wear resistance of the samples produced. One of major advantages of HIP method is that heat and pressure are applied simultaneously during the sintering process. Thus, all or almost all of the pores are eliminated during the manufacturing and a denser material is obtained. During the study, sintering pressure and sintering time were kept constant as 15 min, and also sintering temperature was selected to be 700 and 800 degrees C as the variable parameter. Sintering process was carried out under vacuum starting from the first burn. The produced samples were then prepared metallographically and SEM and EDS analyses were performed for microstructure examinations. Microhardness of the samples was taken to investigate mechanical behaviors of the samples and they were subjected to wear test. Finally, density test was applied to samples and their experimental and theoretical densities were calculated. In conclusion, it was seen that more homogenous samples were obtained as sintering temperature increased. As Co amount and temperature increased in the study, wear resistance increased.
Keywords: hot isostatic pressing; powder metallurgy; microhardness; abrasive wear